A European-wide dataset to uncover adaptive traits of Listeria monocytogenes to diverse ecological niches - Félix, Benjamin; Sevellec, Yann; Palma, Federica; Douarre, Pierre Emmanuel; Felten, Arnaud; Radomski, Nicolas; Mallet, Ludovic; Blanchard, Yannick; Leroux, Aurélie; Soumet, Christophe; Bridier, Arnaud; Piveteau, Pascal; et al. (Scientific data, 2022)
Listeria monocytogenes (Lm) is a ubiquitous bacterium that causes listeriosis, a serious foodborne illness. In the nature-to-human transmission route, Lm can prosper in various ecological niches. Soil and decaying organic matter are its primary reservoirs. Certain clonal complexes (CCs) are over-represented in food production and represent a challenge to food safety. To gain new understanding of Lm adaptation mechanisms in food, the genetic background of strains found in animals and environment should be investigated in comparison to that of food strains. Twenty-one partners, including food, environment, veterinary and public health laboratories, constructed a dataset of 1484 genomes originating from Lm strains collected in 19 European countries. This dataset encompasses a large number of CCs occurring worldwide, covers many diverse habitats and is balanced between ecological compartments and geographic regions. The dataset presented here will contribute to improve our understanding of Lm ecology and should aid in the surveillance of Lm. This dataset provides a basis for the discovery of the genetic traits underlying Lm adaptation to different ecological niches.
Keywords: ekosystém; Listeria monocytogenes; Animals; listeriové infekce; nemoci přenášené potravou; Listeriosis; Foodborne Diseases; zvířata; Ecosystem